Pelatihan Microsoft Word Sebagai Sarana Peningkatan Kompetensi Digital Di SMK Ibrahimy 1 Sukorejo - Muhammad Nazril Irham (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
Information and Communication Technology has developed in all fields. Therefore, mastery of information and communication technology (ICT) is a basic need in facing the era of globalization, one of which is computers and Microsoft Word software. Microsoft Word software is very important to use in documenting digitally, especially in the form of text. Its use is increasingly in demand by various groups, especially in the world of work and education. The development of Microsoft Word software every year can make it difficult for students to keep up with its development. In terms of word processing, the existence of Microsoft Word software can have a significant impact on the development of information and communication technology. SMK Ibrahimy 1 Sukorejo is a vocational school under the auspices of the Salafiyah Syafi'iyah Sukorejo Situbondo Islamic Boarding School. Therefore, a Community Service activity was held at SMK Ibrahimy 1 Sukorejo, which was formed around the concept of Microsoft Word training to improve digital competence and knowledge about the development of information and communication technology among SMK Ibrahimy 1 Sukorejo students.